The application of the lean innovation aproach in the stage-gate model - Guimarães, Levi da Silva (2014)
Innovation has become over the last decades an essential factor for survival of the organizations. Its scope and its its importance includes not only technological aspects but also the administrative area, with the clear objective of increasing competitiveness, thereby making the mission to innovate not only the responsibility of a single area, but the responsibility of all employees in all areas. Accelerated competition has pushed companies to use innovation management tools in research and new product development. Although several models exist in the literature of innovation management, with regard to new product development, there is room for improvement in the management of innovation, from idea generation until product launch. This paper seeks to identify an alternative for improving innovation management, buiding on the stage-gate model, and using the concept of lean innovation, which is a new approach toward the management of the innovation process, based on the concepts of the Toyota Production System. With the use of the lean innovation aproach during some stages of the stage-gate model, it is possible to achieve results in time and cost reduction in new product development.